2018
DOI: 10.1051/matecconf/201819303048
|View full text |Cite
|
Sign up to set email alerts
|

Effective binder based on the artificial anhydrite for manufacturing of filling mixtures

Abstract: Abstract. The article exposes the results of research on the development of filling mixtures based on artificial anhydrite obtained after the interaction of concentrated sulfuric acid and limestone flour. The anhydrite derivation method has a significant impact on its properties and brings more options for the application. The key features of artificial anhydrite are high compressive strength which is more than 50 MPa and extended setting time which is more than 10 hours. In order to use it as a binder in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Thus, it was confirmed that for materials with different structures, it is necessary to select their own additives‐activators. The obtained results were close to those of the anhydrite binder derived from pure sulfuric acid and limestone flour 26 . The authors obtained an anhydrite binder as a mixture of 5% Portland cement CEM I 42.5 and 1% of potassium sulfate, where 100% is the mass of binder.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Thus, it was confirmed that for materials with different structures, it is necessary to select their own additives‐activators. The obtained results were close to those of the anhydrite binder derived from pure sulfuric acid and limestone flour 26 . The authors obtained an anhydrite binder as a mixture of 5% Portland cement CEM I 42.5 and 1% of potassium sulfate, where 100% is the mass of binder.…”
Section: Resultssupporting
confidence: 78%
“…7). The experimental results showed higher values compared both to natural and thermal anhydrite 26,27 …”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations